Characteristics of role models who influenced medical residents to choose surgery as a specialty: exploratory study - Piccinato, Carlos Eli; Rodrigues, Maria de Lourdes Veronese; Rocha, Laura de Andrade; Troncon, Luiz Ernesto de Almeida (São Paulo Medical Journal, 2017)
CONTEXT AND OBJECTIVE: Choosing a medical specialty and making decisions concerning a career are difficult processes for medical students and newly graduated physicians. This exploratory study aimed to investigate the influence of role models on the choice of surgery as a career, and to determine the most influential model characteristics. DESIGN AND SETTING: Qualitative analysis on responses to a self-administered questionnaire, in different teaching-learning settings. METHODS: Residents from all years of various surgical subspecialties in a university hospital were included in a survey about the factors that determined their choice of surgery. The questions included items on whether a role model had influenced them in choosing surgery, and the personal or professional characteristics of the models that had been most influential. The responses were subjected to qualitative content analysis. RESULTS: Sixty-four out of 96 medical residents participated. Fifty-three residents (82.8%) acknowledged the influence of role models. Sixteen model characteristics were indicated as important, with 136 mentions. Characteristics classified as technical skills (55%), such as “medical knowledge” and “manual dexterity” predominated over humanistic characteristics (35%), such as “patient-physician relationships” and “ethical behavior”. However, this difference was not statistically significant (Fisher test, P = 0.11). There were no age differences regarding the proportions mentioning “technical” and “non-technical” attributes, but female residents mentioned significantly more technical skills than their male colleagues did. CONCLUSIONS: The influence of role models seems to be an important factor determining the choice of surgery as a career. The influential characteristics of the models include not only technical but also humanistic qualities.